Pyranoanthocyanin Derived Pigments in Wine: Structure and Formation during Winemaking - Ana Marquez; María P. Serratosa; Julieta Merida (Journal of Chemistry)
In recent years many studies have been carried out on new pigments derived from anthocyanins that appear in wine during processing and aging. This paper aims to summarize the latest research on these compounds, focusing on the structure and the formation process. The main pyranoanthocyanins are formed from the reaction between the anthocyanins and some metabolites released during the yeast fermentation: carboxypyranoanthocyanins or type A vitisins, formed upon the reaction between the enol form of the pyruvic acid and the anthocyanins; type B vitisins, formed by the cycloaddition of an acetaldehyde molecule on an anthocyanin; methylpyranoanthocyanins, resulted from the reaction between acetone and anthocyanins; pinotins resulted from the covalent reaction between the hydroxycinnamic acids and anthocyanins; and finally flavanyl-pyranoanthocyanins. On the other hand, the second generation of compounds has also been reviewed, where the initial compound is a pyranoanthocyanin. This family includes oxovitisins, vinylpyranoanthocyanins, pyranoanthocyanins linked through a butadienylidene bridge, and pyranoanthocyanin dimers.